Screening and Characterization of Biofilm Forming Food Pathogens and their Biocontrol: Life Sciences-Biotechnology for Prospective Medical Science - M Flory Shobana; Roshna Wilson; M P Ayyappa Das; V Subha Priya; K Vivekanandhan; V Manon Mani (International Journal of Life Science and Pharma Research, 2022)
Microorganisms grow as a complex aggregation on a solid substrate to form a biofilm. This film serves as a defensive tool for various pathogenic microorganisms at different stress conditions. A well developed biofilm forms a complex diverse structure of dormant and active bacterial colonies with their enzymes and its excretory products. The main features of biofilm forming bacteria are their ability for surface attachment, high population density and extracellular polymeric substances. Biofilm has positive effects on biotechnology but it is extremely harmful in industry and medicine. Numerous chronic infections are caused by bacterial biofilm. Besides, biofilm also causes various infections of biomaterial used in medicine such as intravascular urethral catheters, orthopedic devices, contact lenses, heart valves and vocal cord prosthesis. Biomaterials used in medicine such as intravascular urethral catheters, orthopedic devices, contact lenses, heart valves and vocal cord prosthesis also gets infected by biofilm. The proposed work was carried out to study the biofilm-forming ability of bacteria from different food items. These bacteria were isolated and tested for biofilm-forming ability using Congo red and microtiter plate assay. All strong biofilm producers were tested for antibiotic sensitivity. Enzyme profiling and molecular characterization were done. Morphological and biochemical characterization of isolates was also carried out.